Strategi Pengembangan Platform Global Transaction Syariah (GTS) dengan Design Thinking, Co-Creation dan Agile Software Development - Setiawan, Fajar Ari; Wahyurini, Octaviyanti Dwi (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Banks are no longer a place where customers attend and make transactions, but banks are something that customers do. This is a response to the rapid advances in technology that have an impact on banking services. The aim of this research is to develop the quality and capability of the Global Transaction Sharia Platform (GTS) by taking a case study at Bank Syariah Indonesia (BSI). This research combines the Design Thinking approach with the Double Diamond Method, Co-creation and Agile Software Development (ASD). Design Thinking with the Double Diamond method is used to understand customer needs and develop appropriate features, Co-creation is the application of collaboration with various stakeholders in carrying out the design process, while ASD is used for rapid development. The results of this research are the development of the GTS platform which will provide solutions to customer transaction needs and increase bank transaction platform capabilities. The Co-creation and ASD approach can make the GTS development process produce a good platform/product with fast process.